2016
DOI: 10.1136/jclinpath-2015-203482
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in melanoma: an update with a focus on current targeted therapies

Abstract: Angiogenesis plays a crucial role in melanoma metastasis and progression. In recent years, numerous studies have investigated the prognostic and clinical significance of this phenomenon, and the development of molecular techniques has enabled us to achieve a better understanding of angiogenesis in melanoma. Herein, we review the current state of knowledge regarding angiogenesis in melanoma, including the pathophysiological, histological and immunohistochemical aspects of this phenomenon. We also review the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 127 publications
(128 reference statements)
0
52
0
1
Order By: Relevance
“…Currently, clinical trials are evaluating whether antiangiogenic treatment in combination with immunotherapy or conventional chemotherapy can improve survival for patients with malignant melanoma [8]. The present study demonstrates that properdistatin treatment improves vascular function, suggesting that this treatment may increase the uptake of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Currently, clinical trials are evaluating whether antiangiogenic treatment in combination with immunotherapy or conventional chemotherapy can improve survival for patients with malignant melanoma [8]. The present study demonstrates that properdistatin treatment improves vascular function, suggesting that this treatment may increase the uptake of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 58%
“…Several strategies have been developed to inhibit angiogenesis, including targeting of angiogenic stimulators or their receptors with monoclonal antibodies or tyrosine kinase inhibitors [46], and treatments with endogeneous angiogenic inhibitors or small peptides that mimic these inhibitors [7]. Some of these strategies have been evaluated in clinical trials, but none of the antiangiogenic treatments have been shown to improve survival for patients with malignant melanoma when used as monotherapy [8]. Currently the effect of antiangiogenic treatment in combination with conventional chemotherapy or immunotherapy is evaluated for patients with malignant melanoma [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of endogenous angiogenic inhibitors or small peptides that mimic these inhibitors [2], and inhibition of angiogenic stimulators or their receptors by using monoclonal antibodies or tyrosine kinase inhibitors [35]. There is substantial evidence that melanoma progression requires angiogenesis [6, 7]. Accordingly, several antiangiogenic agents have been tested in clinical trials but none of the agents have improved survival for patients with malignant melanoma when used as a single treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that melanoma progression requires angiogenesis [6, 7]. Accordingly, several antiangiogenic agents have been tested in clinical trials but none of the agents have improved survival for patients with malignant melanoma when used as a single treatment [7]. Currently, clinical trials are evaluating whether antiangiogenic treatment in combination with immunotherapy or conventional chemotherapy can improve survival for patients with malignant melanoma [7].…”
Section: Introductionmentioning
confidence: 99%